Covid-19 and its impact on digital marketing - Ahmad Effendi, Farah Adibah; Harun, Amran; Farradia, Yuary; Abdul Rashid, Umi Kartini; Abu Seman, Noor Aslinda; Hasim, Muhammad Asyraf (Penerbit UTHM, 2022)
The coronavirus disease 2019 (COVID-19), is a new type of coronavirus spreading exponentially globally. It was started in December 2019 in Wuhan, China, which caused severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (Dashraath et al., 2020 & Chowdhury et al., 2020). Coronaviruses were identified in 1960, which is that everyone will be affected once in life, mostly a young child and more common during fall and winter (D. Bhargava, 2020). SARS-CoV-2 is one of seven types of coronaviruses, including the ones that cause severe diseases like Middle East Respiratory Syndrome (MERS) and Sudden Acute Respiratory Syndrome (SARS). Those affected will experience infection in the nose, sinuses, or upper throat. But Covid-19 will affected upper respiratory tract (sinuses, nose and throat) or lower respiratory tract which is windpipe and lungs (Pathak, 2020).